Documentary Heritage of 1773–1923 of Siberian Archives with Significance to Lithuania - Bilotas, Viktor (Knygotyra, 2022)
Extensive archival documentation related to Lithuania and Lithuanians is kept in Russia, and not only in St. Petersburg or Moscow. Archival cases of Lithuanians containing high numbers of ego-documents, are dispersed throughout the vast territory, and are especially numerous in the Siberian memory institutions. Thanks to the project Lithuanian Sibiriada, copies of documents brought from Tobolsk, Tomsk, Krasnoyarsk and Irkutsk can be found in the Lithuanian State Historical Archives. By using the analysis of documents and the method of classification, this article tries to systematize the information about the relevant materials found in the state archives of Siberia and to determine their typology. The studied documentation covering the period between 1773 and 1923 was found to belong to such areas of public life as politics, economics, science, education, culture, religion, administration, law, statistics, labor, and migration. These are documents (ranging from drafts and copies to official originals) produced by Lithuanians themselves, scribes, state officials not only in Siberia, but also in Lithuania, St. Petersburg or other parts of the Russian Empire. By type, among the discovered documents, there are decrees and manifests, deportation sentences, appointment letters, certificates, sheets, decisions, court records, lists, metrics, reports, reviews, statistics, financial documents. In terms of ego-documents, letters, requests, complaints, explanations, and wills can be found. With such texts, people sought to report, ask, defend themselves or those close to them, or bequeath property. The government created documents with the purpose of informing, registering, taxing, deporting, liberating, accommodating, employing, accumulating data; (not) issuing permits, allowances, salaries. Photos were taken for the mass media, identification, or inspection. Siberian documents touch on such topics as the uprisings, the annexation of the Grand Duchy of Lithuania, attempts of Russification, exiles and prisoners, police surveillance, deaths, liberation, return to the social group, employment, marriage, obtaining a passport, business, resettlement, return to Lithuania. Documentary testimonies are available about free Lithuanians in Siberia: workers and farmers, students and teachers, businesspeople and craftsmen, doctors and priests, officials and various specialists, war refugees and repatriates. The addressees of the letters were the governors’ offices, directorates, courts, various institutions, officials, private people. The study showed that, between 1773 and 1923, Siberian documents about Lithuanians most frequently concern the deported persons (political, criminal), their data and applications. Yet, there are also archival cases significant for the history of Lithuania about the Lithuanian colonies, various specialists, famous personalities, businesspeople, about events in Lithuania itself.